Longitudinal Strain Assessment Of Myocardial Dysfunction In Covid-19 Patients: Correlating Clinical Symptoms And Laboratory Results At Admission And Four Months Post-Treatment - Liastuti, Lies Dina; Tanto, Ines Vidal; Rachman, Aditya; Robot, Marselly Maria; Dwiputra1, Bambang; Ariani, Rina; Danny, Siska Suridanda; Taofan, Taofan; Sukmawan, Renan (Jurnal Kardiologi Indonesia, 2024)
Background: Myocardial dysfunction is increasingly recognized as a complication of COVID-19 infection, with implications for patient prognosis and long-term cardiovascular health. Longitudinal strain, measured via echocardiography, is a sensitive marker of myocardial function that may provide valuable insights into cardiac involvement in COVID-19 patients. This study aimed to assess myocardial dysfunction using longitudinal strain analysis in COVID-19 patients, correlating clinical symptoms and laboratory results at admission and four months post-treatment. Methods : This study compared clinical and laboratory parameters in COVID-19 patients post-recovery with and without myocardial dysfunction. Adult COVID-19 survivors were included if they were hospitalized and met certain criteria. Independent variables included clinical factors and laboratory factors at admission, while the dependent variable was myocardial dysfunction assessed through longitudinal strain of the left and right ventricles on speckle tracking echocardiography. The study was conducted at the Harapan Kita Heart and Blood Vessel Center (RSJPDHK - FKUI)/Department of Cardiology and Vascular Medicine, Faculty of Medicine, University of Indonesia, Jakarta. Results: This study examined the cardiovascular health of 162 participants three months after getting infected with COVID-19. Those with comorbidities had the lowest LV GLS levels. Admission factors like obesity, SpO2, and PaO2 levels were linked to decreased LV GLS levels. These findings suggest that these admission factors may predict the progression of COVID-19 syndrome and its implications on cardiovascular health. Conclusion: COVID-19 patients with cardiovascular comorbidities have lower LV-GLS values. CAD status during admission affects LV GLS values 3-6 months after COVID-19 infection, indicating myocardial dysfunction. Basal lateral LV-GLS correlates with obesity status, SpO2, and PaO2 during admission. Closely monitor COVID-19 patients with cardiovascular comorbidities and recognize the implications of CAD status on myocardial function post-infection.